Scientific imperialism and the proper relations between the sciences - Clarke, S; Walsh, A (2009)
John Dupré argues that 'scientific imperialism' can result in 'misguided' science being considered acceptable. 'Misguided' is an explicitly normative term and the use of the pejorative 'imperialistic' is implicitly normative. However, Dupre has not justified the normative dimension of his critique. We identify two ways in which it might be justified. It might be justified if colonisation prevents a discipline from progressing in ways that it might otherwise progress. It might also be justified if colonisation prevents the expression of important values in the colonised discipline. This second concern seems most pressing in the human sciences. © 2009 Open Society Foundation.